Substrata Uralica : Studies on Finno-Ugrian Substrate in Northern Russian Dialects - Saarikivi, Janne (Helsingin yliopisto, 2010)
The thesis consists of five articles and an introduction. It treats the problems of the Uralic substrate, most notably, the substrate toponyms, in the Russian dialects of Arkhangelsk region. The articles contribute to the general linguistic discussion concerning the nature of linguistic substrate and the outcome of language shift and to the onomastic discussion concerning the etymologisation and ethnic interpretation of substrate toponymy. Among the questions the articles scrutinised are the following: 1) How may phonetic and morphosyntactic substrate interference be verified? 2) How typical is the transfer of vocabulary in the case of a language shift? 3) How the borrowing of toponymy and appellative vocabulary are connected in the case of a language shift? 4) How does the etymologisation of the toponyms differ from the etymologisation of appellatives? 5) How reliable can the toponymic etymologies be? 6) How can the substrate language be identified? It is found that the substrate interference that can be meaningfully studied, from the point of view of historical linguistics, is predominantly lexical and not related to phonetics and morphosyntax, as presumed in many handbooks. New methods are outlined for the identification of substrate languages separately from the lexical, phonological and typological point of view by using the substrate toponymy as the main source of information on extinct languages. A reliability scale for the toponymic etymologies is developed that helps to identify the kinds of etymologies containing ethnohistorically meaningful information. The study also sheds light on questions related to Uralistics and Slavistics. The most important of these are the following: 1) Which Uralic languages were spoken in North Russia prior to Slavic? 2) When did the Slavicisation of the Finno-Ugrian population take place in the area of the Arkhangelsk Region? 3) What is the significance of the Finno-Ugrian substrate in northern Russian dialects to comparative Uralistics? 4) Are there any traces of ...